The effect of various bulk filling techniques on the mechanical and structural characteristics of class I biomimetic composite dental fillings - Alexandra Kemény; Péter Zoltán Farkas; Borbála Leveles; Levente Borhy; Dóra Károly; Tamás Bubonyi; András Volom; Gábor Braunitzer; David S. Alleman; Balázs Varbai (Scientific Reports)
Abstract Tooth degradation develops easily over time from initial caries to deeper cavities. The quality and durability of restorations are crucial in a patients’ life, and it is primarily determined by the mechanical properties of the restorations. Clinicians and engineers apply biomimetic science in dentistry to mimic the natural design of the teeth and emphasize careful material selection as well as bond strength between the tissue and artificial material. The aim of this research was to develop and compare five different bulk filling restoration techniques for high C-factor (5.0) Class I cavities and determine the most durable technique. Tensile bond strength between the dentin and the filling, as well as the inner structure of the filling was measured via computed tomography, scanning electron microscopy and mechanical testing methods. It was found that the semi-direct bulk filling technique (bulk filling with an extra, indirect curing step) can increase the tensile bond strength on average by 58% (51.1 ± 12.2 MPa) compared to the direct bulk filling method with the same materials (32.4 ± 8.2 MPa). The introduced semi-direct technique allows bulk filling to be used on Class I cavities while achieving a high bond strength, resulting in highly durable and reproducible restorations.